The Implementation of Ta’awun Concept in Wahdah Inspirasi Zakat to Diminish the Poverty in Makassar City - Yolleng, Asrum; Wahid Haddade, Abdul; Fatmawati, Fatmawati (International Journal of Islamic Studies, 2023)
This study discusses implementing the ta’awun concept in Wahdah Inspirasi Zakat to diminish poverty in Makassar and how to distribute the results of the ZIS collection to help the community. This study was a qualitative descriptive research with a phenomenological approach. The phenomenological approach is considered appropriate according to the research objective to uncover the core of a phenomenon. It was also based on obtaining a clear view of implementing the ta’awun concept in Wahdah Inspirasi Zakat to diminish poverty in Makassar City. This study used observation, interviews, and documentation to collect the necessary data. The data collection was then processed using data reduction techniques, data presentation, and conclusion. The results showed that Wahdah Islamiyah is a facilitator or liaison for the community who can donate and help other people, especially those related to the economy so that the concept of ta’awun can be achieved. Wahdah Inspirasi Zakat implemented the concept of ta’awun through various programs.